Characterization of Global Research Trends and Prospects on Prone Positioning in Respiratory Failure: Bibliometric Analysis - Rong Lei; Feng Yue; Chaofu Yue; Zihan Zhang; Xian Huang; Qiaolin Li; Zhigang Yang; Rong Li; Keyi Zhao; Mei Yang (Interactive Journal of Medical Research, 2025)
Abstract BackgroundProne positioning has emerged as a crucial intervention in managing acute respiratory failure, especially in acute respiratory distress syndrome and patients with COVID-19. Given the increasing interest in this field, it is important to characterize global research trends and key contributors to identify future research directions. ObjectiveThis study aimed to analyze global research trends, collaboration networks, and research hotspots related to prone positioning in respiratory failure through a comprehensive bibliometric analysis. MethodsBibliometric analyses were conducted using CiteSpace and Biblioshiny software on publications up to December 31, 2023, from the Web of Science Core Collection, focusing on prone positioning in respiratory failure. ResultsA total of 1263 research articles were identified, published in 50 countries by numerous institutions. The United States, France, and Germany contributed the most publications, with the United States producing 21.9% (275/1263) of the total. Key authors such as Claude Guerin and Luciano Gattinoni were identified as major contributors to the field. Keyword co-occurrence analysis revealed the dynamic nature of prone positioning research in respiratory failure. It highlighted protective ventilation and COVID-19-related acute respiratory distress syndrome as emerging hotspots, indicating a shift in focus during the pandemic. ConclusionsThis study revealed a rapidly growing body of literature on prone positioning in respiratory failure, especially in the context of COVID-19. The findings underscore the importance of further multicenter clinical trials to validate current practices and refine treatment protocols. In addition, the application of prone positioning in non-intubated patients represents a potential future research direction.